2020
DOI: 10.22541/au.159986506.61880487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupling effects of topography and the spatial distribution of cypress on surface runoff coefficient on a steep forested slope in southwest China

Abstract: Interactions between topography and the spatial distribution of cypress give rise to the spatial heterogeneity of surface runoff on steep forested slopes in southwest China. To reduce surface runoff and improve the water conservation capacity of cypress forests, the coupling effects of topography and the spatial distribution of cypress on surface runoff coefficient were studied through the Structural Equation Modeling (SEM) and the Response Surface Method (RSM) based on twelve natural runoff plots. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Some tests have shown that groundwater infiltration decreases as the slope increases [41][42][43][44][45][46][47]. Zhu et al showed that each effect factor on the seepage field plays the strongest role on the slope toe, a weaker role on the middle part of the slope, and the weakest role on the top slope [48].…”
Section: Comparison Of Flow Velocities and Topographymentioning
confidence: 99%
“…Some tests have shown that groundwater infiltration decreases as the slope increases [41][42][43][44][45][46][47]. Zhu et al showed that each effect factor on the seepage field plays the strongest role on the slope toe, a weaker role on the middle part of the slope, and the weakest role on the top slope [48].…”
Section: Comparison Of Flow Velocities and Topographymentioning
confidence: 99%